Editorial: liver transplantation in patients with non‐alcoholic fatty liver disease and obesity—authors' reply. Issue 4 (14th July 2017) - Barone, M.; Viggiani, M. T.; Losurdo, G.; Principi, M.; Leandro, G.; Di Leo, A.
Abstract : Linked Content This article is linked to Townsend and Newsome et al and Barone et al papers. To view these articles visithttps://doi.org/10.1111/apt.14179 andhttps://doi.org/10.1111/apt.14195 .